THE SOCIOLOGICAL CONCEPT OF THE STRANGER AND ITS METHODOLOGICAL USE IN LITERATURE - Kay Cook (Politeknik Negeri Jakarta, 2022)
This article aims to demonstrate the methodological approach I took on my research about the sociological term “Stranger” and its expression in literary terms. I deconstruct the term “Stranger”, since it was coined in 1950, analyzing sociological and cultural theories which address the concept: foreigner, immigrant, alien, outsider, pariah, marginal. Although all these deal with the point of view of identity, the definition of Stranger lies primarily in the difference between the “other” versus a group. This binary thinking can be conditioned by geography or bring about discomfort as the Stranger is seen by the group as someone who does not belong to their circle. I found these concepts reflected in post-colonial novels, where notions of identity and the Stranger mingle, in the struggle between the dominant outsider and the submissive colonized people. Since Stranger may be an acquired condition and its status is not rigid, for it is a given characteristic rather than a natural one, I followed a methodological cross-cultural comparison of the term Stranger in both a diachronic and synchronic perspectives. This project deals with cross-cultural identities and contributes to highlight the notion of the Stranger in literature.